A Review of the Relationship Between Islamic Banks and Financial System Stability - Prihatama, Muhammad Iqbal; Wirantakusuma, Dimas Bagus; Saputra, Dimas; Indurasmi, Vaniasda (Journal of Advances in Accounting, Economics, and Management, 2024)
This study seeks to discuss the relationship between Islamic banks and financial system stability using the Scopus database from 2017 to 2023 to provide a clear picture of the concept of the relationship in theory. The research also provides recommendations on potential subjects to study and develop further. There were 10 articles analyzed through bibliometric analysis using the VOSviewer software, which allows the display of visualized patterns, such as the simultaneous occurrence of keywords. The researchers found many results, including key information on the article, sources, and relevant authors. These findings will be very useful as a reference in future research on Islamic banks and financial system stability.